Proteomic analysis identifies key differences in the cardiac interactomes of dystrophin and micro-dystrophin. Issue 14 (5th May 2021) - Wang, Hong; Marrosu, Elena; Brayson, Daniel; Wasala, Nalinda B; Johnson, Eric K; Scott, Charlotte S; Yue, Yongping; Hau, Kwan-Leong; Trask, Aaron J; Froehner, Stan C; Adams, Marvin E; Zhang, Liwen; et al.
Abstract: ΔR4-R23/ΔCT micro-dystrophin (μDys) is a miniaturized version of dystrophin currently evaluated in a Duchenne muscular dystrophy (DMD) gene therapy trial to treat skeletal and cardiac muscle disease. In pre-clinical studies, μDys efficiently rescues cardiac histopathology, but only partially normalizes cardiac function. To gain insights into factors that may impact the cardiac therapeutic efficacy of μDys, we compared by mass spectrometry the composition of purified dystrophin and μDys protein complexes in the mouse heart. We report that compared to dystrophin, μDys has altered associations with α1- and β2-syntrophins, as well as cavins, a group of caveolae-associated signaling proteins. In particular, we found that membrane localization of cavin-1 and cavin-4 in cardiomyocytes requires dystrophin and is profoundly disrupted in the heart of mdx 5cv mice, a model of DMD. Following cardiac stress/damage, membrane-associated cavin-4 recruits the signaling molecule ERK to caveolae, which activates key cardio-protective responses. Evaluation of ERK signaling revealed a profound inhibition, below physiological baseline, in the mdx 5cv mouse heart. Expression of μDys in mdx 5cv mice prevented the development of cardiac histopathology but did not rescue membrane localization of cavins nor did it normalize ERK signaling. Our study provides the first comparative analysis of purified protein complexes assembled in vivo by full-length dystrophin and a therapeutic micro-dystrophin construct. This has revealed disruptions in cavins and ERK signaling that may contribute to DMD cardiomyopathy. This new knowledge is important for ongoing efforts to prevent and treat heart disease in DMD patients.